Hubungan serum seng dengan jumlah CD4 pada lansia di Panti Jompo - Sugeng, Maria Widijanti; Adriani, Merryana; Wirjatmadi, Bambang (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2013)
Background: Elderly people tend to have higher susceptibility to infections because of immune dysfunction, especially cell-mediated immune system which is related to zinc deficiency. Zinc has an important role in the cell-mediated immune system which can be determined by CD4 count. Objectives: To determine the zinc level in the serum and CD4 count in healthy elderly and the correlation between the zinc level in the serum and CD4 count. Method: This was a randomized cross-sectional study. Twenty seven healthy elderly subjects of both sexes aged 60-90 years were recruited for this study from a senior center. Zinc level in the serum and CD4 count were measured. Result: The average of CD4 count was 710 + 269 cells/ml, and the average of zinc level in the serum was 87,29 + 10,27 Î¼g/dL. Twenty six percent elderly had low CD4 count (<460cells/ml. There was no zinc deficiency among the elderly but 30% elderly had zinc level 70- 80 Î¼g/dL. There was a significant correlation (p<0,05) between zinc level and CD4 count, which was analyzed using Pearson correlation method.Conclusion: CD4 count has correlation with zinc level in the serum in elderlyKeywords: Zinc level, CD4 count, elderly